Study on Short circuit Dynamic Process of Synchronous Generator Based on Matlab Simulation. Issue 6 (April 2019) - Li, Xiaoquan; He, Jiangjiang; Chen, Geng
Abstract: Synchronous generator is a key equipment of power system. It is very important that analyzing exactly the short circuit dynamic process of synchronous generator for the alternator and power system protection. Based on an idealized synchronous generator, this paper analyzes its mathematical equations and builds a software simulation model using Matlab S-function. The simulation study of three phase short circuit is finished. The varieties of main parameters in short circuit dynamic process are revealed vividly by simulation results which prove to be accurate and effective.